Karakterisasi Reservoar Berdasarkan Analisis Inversi Seismik Impedansi Akustik dan Multiatribut Seismik, Studi Kasus: Lapangan Bunyu Tapa, Cekungan Tarakan, Kalimantan Utara - Zalfadhiyaa Faariz Taqiy; Warto Utomo; Muhammad Shidqii; Adi Susilo (BBPMGB LEMIGAS, 2025)
The Tarakan Basin is a hydrocarbon-bearing basin with significant geological complexity. This research in the Bunyu Tapa field aims to characterize the reservoir using the acoustic impedance seismic inversion and multiattribute seismic analysis. Through the approach of seismic inversion of acoustic impedance and multiattribute seismic, it is expected to map well the distribution of reservoir prospect areas in the Bunyu Tapa area based on petrophysical analysis. This research focuses on the Intra Bunyu interval which is part of the Bunyu Formation. The results showed that acoustic impedance inversion of the Intra Bunyu successfully identified variations in reservoir properties. Through linear regression analysis between acoustic impedance and porosity, a negative relationship was found that allows estimation of porosity distribution. This study also analyzed the contribution of multiattribute approach with neural network to validate and enrich the interpretation results. Based on the results of seismic interpretation, seismic inversion of acoustic impedance, and prediction of porosity property distribution based on the linear regression relationship between acoustic impedance and porosity, it is known that the Top Intra Bunyu area is a potential reservoir area with an acoustic impedance value of 3200 - 4800 ((m/s)*(g/cc)) with a porosity value of 5% to 35%. This research contributes to the understanding of the structure and characteristics of reservoirs in the Tarakan Basin, which can support the exploration and exploitation of hydrocarbon resources in the region